Patients' Perceptions of food Service Quality at Royal Prima Hospital Medan - Lidia Marianne Anggreni Simanjuntak; Destanul Aulia; Albiner Siagian (Britain International of Exact Sciences (BIoEx) Journal, 2020)
This study deals with patients' perceptions of food service quality at Royal Prima Hospital Medan. Someone's perception in evaluating the quality of service will greatly affect customer satisfaction. From someone's perception, it will produce a sense of satisfaction or dissatisfaction with the service. And this will greatly affect the desire or willingness to use or use the service. This type of qualitative research will be used is a case study approach with in-depth interviews with informants. The case study approach focuses intensively on one particular object that studies it as a case. Based on HTA assessment that the patient's perception of nutritional service at Royal Prima Hospital is still in accordance with what is expected of the patient's wishes. It can be concluded that the method of serving food at the hospital is good in its implementation, where the waitress in serving food greets the patient by mentioning the patient's identity to adjust whether the diet given is right for the intended patient. Therefore, the assessment based on HTA has met the MOH standards.